2012
DOI: 10.2174/156720512800107564
|View full text |Cite
|
Sign up to set email alerts
|

Altered Calmodulin Degradation and Signaling in Non-Neuronal Cells from Alzheimer’s Disease Patients

Abstract: Previous work indicated that changes in Ca 2+ /calmodulin (CaM) signaling pathway are involved in the control of proliferation and survival of immortalized lymphocytes from Alzheimer's disease (AD) patients. We examined the regulation of cellular CaM levels in AD lymphoblasts. An elevated CaM content in AD cells was found when compared with control cells from age-matched individuals. We did

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…CaM-PI3Kα binding is also supported by observations of altered CaM degradation and signaling in non-neuronal cells from Alzheimer’s disease (AD) patients [32]. The increased levels of CaM synergize with serum to overactivate PI3K/Akt in AD patient cells by direct binding of CaM to p85, leading the authors to suggest that failure of CaM degradation, and thus of Ca 2+ /CaM-dependent signaling, may be important in the development of AD.…”
Section: Cam Interacts Directly With Pi3kαmentioning
confidence: 85%
“…CaM-PI3Kα binding is also supported by observations of altered CaM degradation and signaling in non-neuronal cells from Alzheimer’s disease (AD) patients [32]. The increased levels of CaM synergize with serum to overactivate PI3K/Akt in AD patient cells by direct binding of CaM to p85, leading the authors to suggest that failure of CaM degradation, and thus of Ca 2+ /CaM-dependent signaling, may be important in the development of AD.…”
Section: Cam Interacts Directly With Pi3kαmentioning
confidence: 85%
“…We previously reported increased CaM content in lymphoblasts from AD patients, as a consequence of impaired proteasomal degradation of the protein [19]. The higher CaM content was associated with impaired cell survival/death mechanisms [15,36].…”
Section: Discussionmentioning
confidence: 99%
“…These features were considered peripheral signs of the disease, because current evidence relates the process of neuronal apoptosis occurring in AD to the aberrant re-entry of differentiated neurons into the cell cycle [16-18]. Moreover, we detected significantly increased levels of CaM in AD lymphoblasts [19]. …”
Section: Introductionmentioning
confidence: 99%
“…The Ca 2+ /calmodulin (CaM) signaling pathway was altered in AD lymphoblasts [30]. Esteras et al [30] showed that increased levels of CaM synergize with serum to overactivate PI3K/AKT in AD cells by direct binding of CaM to the regulatory α-subunit (p85) of PI3K.…”
Section: Impaired Ups Function Is Associated With Admentioning
confidence: 99%
“…Esteras et al [30] showed that increased levels of CaM synergize with serum to overactivate PI3K/AKT in AD cells by direct binding of CaM to the regulatory α-subunit (p85) of PI3K. Because CaM degradation is primarily by way of the UPS [31], the impaired UPS impedes CaM degradation and eventually the Ca 2+ /CaM-dependent signaling pathways, which may be important in the etiopathogenesis of AD [30]. …”
Section: Impaired Ups Function Is Associated With Admentioning
confidence: 99%